If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+6x-12=-7x+2x-12+5
We simplify the equation to the form, which is simple to understand
9x+6x-12=-7x+2x-12+5
We move all terms containing x to the left and all other terms to the right.
+9x+6x+7x-2x=-12+5+12
We simplify left and right side of the equation.
+20x=+5
We divide both sides of the equation by 20 to get x.
x=0.25
| -21=y/4 | | 9x-6=3x+6 | | -b=19 | | 6-3x=-5x-2 | | 2x-3x=3-x | | a-16/18=8/9 | | 1/6(5x-9)=7 | | 7-x=6+14 | | 8-4=x+1 | | 6x+4x=10 | | y=x^2*ln(x+2) | | 15x+3y=39 | | 1200=0.18*x | | 1200=0.18x | | -3/4+3/2-2 | | -3x-3x=48-6 | | t^2+7t-18=T+1 | | -19.95-1.10x=-2.35 | | f(x)=3x^3-4x^2 | | 2x^2-5x-38=0 | | y=-2(x-3)+4 | | (2x-5)=1 | | 5/6x=30 | | 7x-1=8x-4 | | 3(2x-3)+5=17 | | 3x+8=8x-22 | | -13-x=-5 | | -5.00-4.00x=53.00 | | 3(x-1)-2(x+4)=10 | | -135-20(x-4)=24x | | 6y^4-12y^3+4y^2= | | 4-x=5x+10 |